A comparative study between povidone iodine and metronidazole for peritoneal lavage in cases of peritonitis - Baig, Asadulla; K., Mohan Kumar (International Surgery Journal, 2019)
Background: Peritonitis secondary to hollow viscous perforation is one of the commonest emergencies encountered in general surgical practice. This randomized study aimed to compare the efficiency of Povidone iodine and Metronidazole in these cases by quantitative analysis of bacterial colony count in patients who have received peritoneal lavage with either of them. Methods: A total of 100 consecutive patients who presented with peritonitis secondary to hollow viscous perforation were enrolled in this study (February 2010 to February 2011) and systematically divided into 2 groups: peritoneal lavage with povidone iodine group and lavage with metronidazole group. The post-operative progress was assessed by comparing the pre-wash and post wash colony counts in both the groups, development of surgical site infection and duration of hospital stay. Results: The median age of the patients was 33 years (range: 12-75 years), with a male: female ratio of 3.8:1. Perforation of duodenal ulcer (67%) was the commonest cause of peritonitis with E. coli (65%) being the commonest organism isolated from the peritoneal fluid. Reduction in bacterial colony count was seen in both the groups of patients, however, there was significantly greater reduction in the patients who received lavage with Metronidazole (p=0.06). Incidence of surgical site infection was less in the Povidone iodine group though it did not reach statistical significance. Conclusions: The use of povidone iodine in peritoneal lavage significantly reduce the bacterial colony and may also result in fewer surgical site infections.